Synthesis of cobalt doped titania nano material assisted by gemini surfactant: Characterization and application in degradation of Acid Red under visible light irradiation - Radha Devi Chekuri; Siva Rao Tirukkovalluri (South African Journal of Chemical Engineering, 2017)
The present work focuses on the synthesis of cobalt doped titania nano material assisted by 1,4-butane sultone anionic gemini surfactant: Co2+-TiO2 (with surfactant). The synthesized nano catalysts were characterized by XRD, UVâVis DRS, XPS, SEM, FT-IR, HR-TEM and BET-surface area analysis. XRD and UV-DRS studies have indicated that all the catalysts synthesized were in anatase phase and red shift was observed with decrease in the band gap energy. XPS analysis of the catalysts has confirmed the presence of cobalt along with TiO2. SEM analysis indicated change in morphology of the particles without any agglomeration. From FTIR studies frequency shift was observed for TiO2 which was due to doping of cobalt into TiO2 lattice. TEM images have shown reduced particle size of Co2+-TiO2 (with surfactant). BET analysis confirmed increase in surface area of the catalyst. From BET analysis Pore volume and pore size was also analyzed. These results emphasize the important role played by the gemini surfactant on the structure and photocatalytic activity of the catalyst synthesized. The photocatalytic efficiency of the synthesized catalyst was investigated by degradation of Acid Red where degradation was completed within 30Â min. Keywords: Cobalt doped titania nanomaterial, Gemini surfactant, Solâgel method, Photocatalysis, Acid Red